Chemotherapeutic Mechanism of Action of the Synthetic Resorcinolic Methyl 3,5-dimethoxy-2-octanoylbenzoate - Correa, Willian Ayala; das Neves, Silvia Cordeiro; Oliveira, Rodrigo Juliano; Kassuya, Cândida A.; Navarro, Stephanie D.; Faustino Martins, Allana Cristina; Saroja, Baby; Mitsuyasu, Barbara [UNESP]; Ostaciana Maia Freitas da Silveira, Ingridhy; Vitor, Neimar; Coelho, Henrique Rodrigues Scherer; Vilela, Marcelo L. B.; et al. (American Chemical Society (ACS), 2024)
Resorcinolic lipids are described as potential examples of selective chemotherapeutic adjuvants that can enhance the effects of cyclophosphamide (CYC) while promoting cell death without causing DNA damage. Therefore, the current study attempted to describe how the resorcinolic lipid methyl 3,5-dimethoxy-2-octanoylbenzoate (AMS35BB) interacted with DNA (DNA docking) and how this compound affected genetic toxicology models and other biological characteristics when combined with CYC. We observed that AMS35BB, used alone (7.5 and 10 mg/kg), increases the frequency of genomic damage (comet assay) but not chromosomal damage (micronuclei assay), lowers phagocytosis, and promotes cell death in Swiss male mice. When used in association with CYC, AMS35BB can reduce the risk of genomic damage by up to 33.8% as well as chromosomal damage, splenic phagocytosis, cell death, and lymphocyte frequency. Molecular docking showed that AMS35BB had a higher affinity than the active metabolite of CYC for binding to the DNA double helix major groove. As a result, AMS35BB has the potential to be both an adjuvant when used in association with CYC and a therapeutic candidate for the development of a selective chemotherapeutic drug.